Architectural Marketing Model to Achieve Iconic Structures - Faysal Abo-Elazm; Basma S. Kassem (Genius Journals, 2024)
Marketing is more than just logos, posters and colors. It's about what you express: telling your story, your vision, and how you want to be perceived. Many of the structures that were constructed did not meet the expected marketing plan for various reasons. Nowadays, the design and promotion of buildings and structures has become necessary to define the image of the city and its position within the map of the world. Eiffel Tower stands as one of the worldwide most iconic structures. resulted from a major design competition therefore, the research presents analysis of Eiffel tower as a case study in order to reach an Architectural marketing model that help architects to measure the ability of architectural structures to become “iconic” to stand out through the fierce competition in the field by using the marketing attributes to be able to create a unique and identifiable strong image to the countries. Subsequently the proposed model applied on Opera Sydney House competition to proof the validation of the model.
Keywords: competition; Sydney; posters